2011
DOI: 10.2134/agronj2010.0273
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Liquid Cattle Manure on Micronutrients Content and Uptake by Corn and their Availability in a Calcareous Soil

Abstract: The effect of soil application of liquid dairy cattle (Bos taurus) manure on Cu, Zn, Fe, Mn, and B content and uptake by corn (Zea mays L.) and their availability in a calcareous soil was studied. The field received 9 yr of liquid cattle manure in two fertilization experiments, initially with winter wheat (Triticum aestivum L.) (1996–2000), followed by a similar experiment with corn (2002–2006). The treatments, practiced on the same plots every year since 1996, included: (i) soil incorporation of liquid dairy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…These indicated that Cu and Zn concentrations in crops were not influenced by soil total or DTPA Cu and Zn. The same outcome was reported for Cu and Zn concentrations in maize following the addition of liquid swine manure (Berenguer et al 2008) and liquid dairy cattle manure (Nikoli et al 2011). Essentially, plant appeared to be capable of restricting heavy metal translocation from soil to roots and internal transport to avoid excessive heavy metal-induced damage (Ahumada et al 2009).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…These indicated that Cu and Zn concentrations in crops were not influenced by soil total or DTPA Cu and Zn. The same outcome was reported for Cu and Zn concentrations in maize following the addition of liquid swine manure (Berenguer et al 2008) and liquid dairy cattle manure (Nikoli et al 2011). Essentially, plant appeared to be capable of restricting heavy metal translocation from soil to roots and internal transport to avoid excessive heavy metal-induced damage (Ahumada et al 2009).…”
Section: Resultssupporting
confidence: 55%
“…According to recent studies, repeated application of poultry litter (Schomberg et al 2008), pig slurry (Novak et al 2004, Berenguer et al 2008 or cattle manure (Lipoth andSchoenau 2007, Benke et al 2008) can substantially increase the Cu and Zn contents in the upper soil layer. Moreover, several researchers have investigated the impact of liquid swine or solid cattle manures on the absorption of Cu and Zn by different plant species (Zhou et al 2005, Hanč et al 2008, Nikoli and Matsi 2011, Legros et al 2013. For example, the result of Lipoth and Schoenau (2007) showed that Cu concentration in the straw of wheat (3.11 mg/kg) at the highest rate of swine effluent was significantly higher than the control (1.90 mg/kg).…”
mentioning
confidence: 99%
“…In any case, increases of these plant parameters are expected after repeated annual applications of LCM to soil for many years and/or at high rates (Evans et al, 1977;Nikoli & Matsi, 2011 Table 2. Field experiments: liquid cattle manure (LCM) application rates, the plant species studied and the duration of the experiment.…”
Section: Effect Of Liquid Cattle Manure Application On Growth Yield mentioning
confidence: 99%
“…Therefore, it can serve directly as a source of micronutrients, upon its use as basal dressing for crops, increasing micronutrients plant uptake and probably concentration (Brock et al, 2006;Nikoli & Matsi, 2011). In addition, an indirect effect of LCM on the availability of the soil native micronutrients cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation